AURICULAR ACUPRESSURE FOR METABOLIC CONTROL IN PATIENTS AT RISK OF METABOLIC SYNDROME: SYSTEMATIC REVIEW AND META-ANALYSIS - Suci Sekarini Martayoga; Nike Estu Renaning Tyas; Antonius Hapindra Kas; Hasan Mihardja (Sean Institute, 2023)
This study was designed to answer questions regarding the effectiveness of auricular acupressure in improving metabolic parameters of patients at risk of metabolic syndrome. Article search was conducted on 4 search engines (Pubmed, EBSCO, ProQuest, and Scopus) on November 20, 2021. Studies with patients at risk of metabolic syndrome, characterized by overweight to obesity, type 2 diabetes mellitus, hypertriglyceridemia, hypercholesterolemia, or hypertension were included in the study. Two authors screened titles and abstracts based on formulated clinical questions. The study quality assessment instrument used was a revised Cochrane RoB tool for randomized trials. There were 11 RCT studies of moderate to good quality. The frequency with which acupressure was performed varies greatly between studies. In general, we found that there was no significant difference in reducing triglyceride levels (p=0.87), waist circumference (p=0.11), systolic blood pressure (p=0.19), diastolic blood pressure (p=0.37) in the control and intervention groups. The decrease in blood sugar levels was recorded to be higher in the intervention group with a mean difference of 14.38 (95% CI, 5.29–24.37). One study only reported HDL outcome, with the result that the increase in HDL in the intervention group was higher than in the control group. Compared with patients who only received standard therapy, patients who received additional auricular acupressure therapy experienced a higher decrease in glucose levels. However, this therapy did not cause a significant difference in the reduction of triglycerides, blood pressure, and waist circumference.